MODERN MECHANISMS OF MANAGEMENT OF INCREASE EFFICIENCY OF INVESTMENTS INTO THE AGRICULTURAL BUILDING ON THE REPUBLIC DAGESTAN EXAMPLE - J. V. Belozertseva; S. G. Gamidov (Вестник Дагестанского государственного технического университета: Технические науки)
Work is devoted the information systems, allowing to automate managerial process by increase of efficiency of investments into agricultural building. The control system of economic object where the choice of mechanisms of management is carried out by increase of efficiency of investments into agricultural building by means of the automated system of the analysis and an estimation of efficiency of investments is developed. Use in spread of knowledge on new information technologies in Republic Dagestan of possibilities of the federal state unitary enterprise «Mail of Russia» is offered.